Exploring the Physical, Mental, and Social Health Issues of Sex Trafficking Victims by Stage of Exploitation - Krushas, Amber E. (Victims & offenders, 2023)
It is well established that experiencing human trafficking is associated with adverse consequences that are oftentimes substantial and enduring, including mental, physical, and social harms. Although health complications are recognized as being an important consideration in the response to victims, little is known about how these effects might vary depending on when victims were exploited or how they compare to individuals who have not experienced trafficking. Using a national sample of 986 young, non-college educated women, the current study seeks to fill this gap by examining the physical, mental, and social health issues of sex trafficking victims by stage of exploitation (i.e., minor only, adult only, both minor and adult) compared to non-sex trafficking victims. Results indicate significant associations between stage of exploitation and current social health issues, with limited significant associations between stage of exploitation and mental and physical health issues. Overall, these preliminary findings suggest that victims may experience different types of health issues based on when they were exploited, which could inform future response efforts.